Movement pattern and population structure of Clibanarius antillensis Stimpson, 1859 in south Brazil - Silva, Alexandre R. da; Santos, Renan A. P. dos [UNESP]; Gryszyszyn, Luana Maria; Paluski, Geovana Bastos; Gregati, Rafael Augusto (Cambridge Univ Press, 2022)
Hermit crabs have soft abdomens and therefore must use empty gastropod shells as protection. Shell choices do not occur at random, and the animals often occupy shells with the best fit among the available ones. To live in intertidal and sublittoral zones, regions subjected to daily variations in abiotic factors, hermit crabs present a locomotory circadian rhythm. Clibanarius antillensis has been the object of several studies in Brazil's south-east, so this study was aimed at describing its population in the south of Brazil and its movement activity under laboratory conditions during night-time and daytime, while using two different shells. The animals were sampled from the Sepultura and Lagoinha beaches, in the state of Santa Catarina through free diving. Sex ratio was skewed for males, with ovigerous females present during the whole year but with a spring peak. Males were more abundant than females, ovigerous females and intersex individuals, being predominant in all size-classes analysed. The hermit crabs occupied mainly two gastropod shells: Cerithium atratum and Agathistoma viridulum, and ovigerous females used only the first. Clibanarius antillensis showed nocturnal activity and the animals using C. atratum shells were more active than those using A. viridulum. Cerithium atratum shells are lighter and less bulky than A. viridulum, implying that there might be a tradeoff in which the hermit crabs use lighter shells, that provide less protection in order to expend less energy and be more active.
Keywords: Hermit crabs; Movement activity; Population structure; Shell choices